THE ROLE OF SITE WWW.AR.MO3JAM.COM TO HELP STUDENTS UNDERSTAND IN ARABIC DIALECTS - Kurniawan, Indra; Massofia, Fitrah Dinanti (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
In recent years, we have witnessed a significant increase in the number of students of Arabic who are not native speakers of the language. This phenomenon also occurred in Indonesia, where people's interest in learning Arabic increased. Literary works such as texts and films have become one of the motivations to continue deepening messages and meanings found in these works. In this context, Arabic dictionaries have an important role in facilitating delivery of the message between the writer, and the reader or viewer. This study uses the methodology of library research, intending to analyze the role and importance of the www.mo3jam.com  dictionary in facilitating understanding of various Arabic dialects in pronunciation and writing according to regional differences. This data collection used is documentation by www.ar.mo3jam.com and data analysis to identify patterns of vocabulary used in the various dialectal contexts of Arabic. The results of this research showed that the www.ar.mo3jam.com  dictionary has features that facilitate use by users, including a list for selecting Arabic dialects from different Arab countries, and a system for arranging vocabulary based on the alphabet system, where each word contains a meaning in Standard Arabic, and each word contains its synonyms in other Arabic dialects.